Referência identificadora: a identificabilidade e a acessibilidade = Identifying reference: identificability and accessibility - Maria Angela de Sousa Bôer (Acta Scientiarum: Language and Culture, 2008)
Este artigo objetiva apresentar o resultado de uma pesquisa sobre os níveis de identificabilidade e de acessibilidade das descrições definidas (DDs), em três textos de literatura oratória. A análise de 537 DDs apresenta fundamentos para o entendimento de que, na linguagem em funcionamento, o processo de nomeação, designação e predicação das coisas é determinado por constituição de saberes com efeito estruturador de sentidos, no texto, entendido como evento discursivo e não por normas aprioristicamente estabelecidas. Current essay provides research results on the identificability and accessibility levels of definite descriptions (DDs) in three texts from rhetorical literature.The analysis of 537 definitedescriptions is based on the understanding that in functional language the process of nomination, designation and prediction of things is determined by the constitution of knowledge systems with the structuring effect of meanings in the text. The latter is taken asa discursive event and not by a priori established norms.